Enjoy this too! 100 streak special!

Calculus Level 5

lim n m = 1 n k = 1 m cos 2 ( π ( 2 k 1 ) 2 ( 2 m + 1 ) ) = A B \large \lim_{n \to \infty}\sum\limits_{m=1}^{n} \prod\limits_{k=1}^{m} \cos^{2} \! \left(\frac{π(2k-1)}{2(2m+1)}\right)=\frac{A}{B}

Find A + B A+B where A A and B B are coprime positive integers.

Inspired by Otto's problem .


The answer is 20.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Otto Bretscher
Sep 3, 2015

What a beautiful and fascinating problem! Thank you!

I worked out a kind of rambling and roundabout solution, late at night... there has to be a better way. Along the way we will use the symmetries cos ( π t ) = cos ( t ) \cos(\pi-t)=-\cos(t) and sin ( π t ) = sin ( t ) \sin(\pi-t)=\sin(t) as well as the formulas for cos 2 ( t ) \cos^2(t) and sin 2 ( t ) \sin^2(t) in terms of cos ( 2 t ) \cos(2t) . All products will be taken form k = 1 k=1 to k = m k=m unless stated otherwise. Let t = π 2 m + 1 t=\frac{\pi}{2m+1} . Then the given product is

1 2 m ( 1 + cos ( ( 2 k 1 ) t ) = 1 2 m ( 1 cos ( 2 k t ) ) \frac{1}{2^m}\prod(1+\cos((2k-1)t)=\frac{1}{2^m}\prod(1-\cos(2kt)) = sin 2 ( k t ) = k = 1 2 m sin ( k t ) = 2 m + 1 4 m . =\prod\sin^2(kt)=\prod_{k=1}^{2m}\sin(kt)=\frac{2m+1}{4^m}.

The last formula has been discussed here .

Now m = 1 2 m + 1 4 m = 11 9 \sum_{m=1}^{\infty}\frac{2m+1}{4^m}=\frac{11}{9} , an arithmetic-geometric series, so that a + b = 20 a+b=\boxed{20}

I'm sorry to report that it is "back to work" for me... classes start after the US "Labour Day".. with a heavy heart I need to say goodbye to Brilliant, but I will be back in December, if all goes well. Thank you for all the fun!

Moderator note:

Aw, we will miss you! Come back in December with a bunch of interesting problems!

You can send your students here for extra credit :)

There is a much easier way.

We can deduce z 2 n + 1 = k = 1 n ( z 2 2 z cos ( ( 2 k 1 ) π 2 n ) + 1 ) z^{2n}+1=\prod\limits_{k=1}^{n}\left(z^2-2z\cos\left(\frac{(2k-1)\pi}{2n}\right)+1\right)

Using z 2 n + 1 = ( z 2 + 1 ) ( 1 z 2 + z 4 . . . + z 2 n 2 ) z^{2n}+1=(z^2+1)(1-z^2+z^4-...+z^{2n-2}) (when n is odd) and plugging z = i z=i . The product written above can be worked out from that by considering odd n.

I'll miss your wonderful problems and solutions Otto.

Isaac Buckley - 5 years, 9 months ago

Log in to reply

Very elegant indeed! Thanks.

Otto Bretscher - 5 years, 9 months ago

Aw, we will miss you! Come back in December with a bunch of interesting problems!

You can send your students here for extra credit :)

Calvin Lin Staff - 5 years, 9 months ago

Log in to reply

Thanks, Calvin! I'm writing my syllabi for the coming semester right now, and I will list Brilliant as a valuable (and fun) resource.

Otto Bretscher - 5 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...